2010
DOI: 10.4236/jmmce.2010.91005
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Microstructures and Mechanical Properties of Al 6061 Alloy and the MMC Al 6061/TiB<sub>2</sub>/12<sub>p</sub>

Abstract: Al 6061 alloy is widely used for commercial applications in the transportation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 13 publications
(17 reference statements)
1
45
0
Order By: Relevance
“…The as-cast alloy morphology has some plate-like structure and evidence of formation of an intermetallic-like phase within the matrix of the alloy ( Figure 5). This plate-like structure has been identified as aluminium-titanium intermetallics with transmission electron microscope [7] while the precipitate-like phase represents TiB 2 [8]. Previous work has shown that TiB 2 reinforcement is both thermodynamically and microstructurally stable within the aluminide matrices [9].…”
Section: Resultsmentioning
confidence: 99%
“…The as-cast alloy morphology has some plate-like structure and evidence of formation of an intermetallic-like phase within the matrix of the alloy ( Figure 5). This plate-like structure has been identified as aluminium-titanium intermetallics with transmission electron microscope [7] while the precipitate-like phase represents TiB 2 [8]. Previous work has shown that TiB 2 reinforcement is both thermodynamically and microstructurally stable within the aluminide matrices [9].…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of mechanical properties of unreinforced Al 6061 alloy and Al 6061/12 wt% Titanium Diboride (TiB2) MMCs manufactured through in-situ process was made. Result revealed that mechanical properties of MMCs were higher than unreinforced alloy [4].The tensile strength of Al/5 Vol. % of Silicon Carbide (SiC) composite fabricated by stir casting route was found high than the same composite fabricated by powder metallurgy technique [5].…”
Section: Introductionmentioning
confidence: 86%
“…An attempt was made to synthesize the in-situ composite withA356 as matrix material and TiB 2 as the reinforcement eliminating the inherent associated defects with exsitu process like agglomeration, poor wettability and nonuniformity of distribution. The as-cast aluminium based reinforced composites requires to be heat treated for enhancing its mechanical properties (5).Nevertheless, the synergic impact of heat treatment and the kind of reinforcement plays a huge part in dictating the final mechanical properties of composites (6). The microstructure was used to confirm the size and uniformity of TiB 2 particles.…”
Section: Introductionmentioning
confidence: 99%